2018
DOI: 10.1002/ange.201804309
|View full text |Cite
|
Sign up to set email alerts
|

A Reversible Fluorescent Probe for Real‐Time Live‐Cell Imaging and Quantification of Endogenous Hydropolysulfides

Abstract: The chemical biology of reactive sulfur species, including hydropolysulfides,h as been as ubject undergoing intense study in recent years,but further understanding of their "intact" function in living cells has been limited owing to alack of appropriate analytical tools.I no rder to overcome this limitation, we developed an ew type of fluorescent probe that reversibly and selectively reacts to hydropolysulfides.T he probe enables live-cell visualization and quantification of endogenous hydropolysulfides withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Since incorporation of 4-fluorobenzenesulfonamide transformed rhodamine 500R into a highly fluorogenic SNAP-tag probe (23), we also applied this structural change to CPY to obtain 32 (Figure 6e). We then measured the absorbance and fluorescence increase of 32 upon binding to the SNAP-tag in-vitro and compared its fluorogenicity to the original CPY SNAP-tag probe (30). Despite a reduced brightness, 32 yielded a significantly increased turn-on in the presence of the SNAP-tag compared to 30 (Figure 6f).…”
Section: Extending the Strategy To Other Rhodamine-based Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since incorporation of 4-fluorobenzenesulfonamide transformed rhodamine 500R into a highly fluorogenic SNAP-tag probe (23), we also applied this structural change to CPY to obtain 32 (Figure 6e). We then measured the absorbance and fluorescence increase of 32 upon binding to the SNAP-tag in-vitro and compared its fluorogenicity to the original CPY SNAP-tag probe (30). Despite a reduced brightness, 32 yielded a significantly increased turn-on in the presence of the SNAP-tag compared to 30 (Figure 6f).…”
Section: Extending the Strategy To Other Rhodamine-based Dyesmentioning
confidence: 99%
“…12,17 Xanthenes with reduced electron density are also known to display enhanced reactivity towards intracellular nucleophiles, which can decrease fluorophore brightness. 16,[29][30] Furthermore, modification of the xanthene core often requires multi-step syntheses and the development of sophisticated methodologies. 8,12,[31][32] With respect to probes for SMLM techniques, stable rhodamine spirolactams were previously introduced which could be photoactivated to form a fluorescent state.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figures 4a, 4b, 4d, and 4e, when the cells were stimulated with LPS, IFN-γ, and PMA, the fluorescence of the red channel was enhanced compared with that of the green channel. Next, we added TEMPO and GREs, which produce GSH, 59,60 to the cells after stimulation with LPS, IFN-γ, and PMA, and the imaging experiments were performed 30 min later. The results indicated that the fluorescence in the red channel was weaker than that in the green channel and the F R / G value was lower (Figures 4b, 4c, 4e, and 4f).…”
Section: Reversible Sensing Of Intracellular Exogenous and Endogenous Onoo − And Gsh Using Ucnps-1@pei@nb3mentioning
confidence: 99%
“…As shown in Figure 4A-B and Figure 4D-E, when the cells were stimulated with LPS, IFN-γ, and PMA, the fluorescence of the red channel was enhanced compared to that of the green channel. Next, we added TEMPO and GSH reduced ethyl ester (GREs), which produce GSH, 59,60 to the cells after stimulation with LPS, IFN-γ and PMA, and the imaging experiments were performed 30 min later. The results indicated that the fluorescence in the red channel was weaker than that in the green channel and the F R / G value was lower (Figure 4B-C and 4E-F).…”
Section: Reversible Sensing Of Intracellular Exogenous and Endogenous Onooand Gsh Using Ucnps-1@pei@nb3mentioning
confidence: 99%